Work placement learning and student employability: Do student satisfaction, commitment and achievement matter?. Issue 6 (December 2022) - Otache, Innocent; Edopkolor, James Edomwonyi
While the extant literature generally suggests a positive relationship between work placement learning (WPL) and student employability, the mechanisms underlying this relationship remain unclear and under-researched. Against this background, this study draws on insights from experiential learning and self-determination theories to explore the mediating effects of student satisfaction, commitment and achievement on the relationship between WPL and student employability. The study adopted a quantitative approach, gathering data from 294 students in two public higher education institutions (HEIs) in Nigeria using a structured questionnaire. A serial mediation analysis was performed to test the study hypotheses. The results show that WPL is positively associated with student satisfaction, commitment, achievement and employability. The results also indicate that student satisfaction, commitment and achievement have strong positive impacts on student employability. Further analysis reveals that student satisfaction, commitment and achievement individually and sequentially mediate the relationship between WPL and student employability. This research demonstrates that student satisfaction, commitment and achievement help to maximize the positive impact of WPL on employability. The findings offer policy and practical implications for HEIs, policymakers, students and industry.